2019
DOI: 10.1061/(asce)mt.1943-5533.0002944
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Strength Development of Sodium Carbonate–Activated Blast Furnace Slags

Abstract: This paper presents the study of alkali activated slags where sodium carbonate acts as a primary activator. The slow activation mechanism of sodium carbonate is accelerated by sodium hydroxide and with traces of calcium hydroxide. Strength development and the progress of hydration of the mixes are studied with the phase transformation and development of microstructural features through quantitative techniques such as thermogravimetric analysis and phase-identification techniques such as Fourier transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Compared to Na 2 SiO 3 , sodium carbonate (Na 2 CO 3 ) can be a promising substitution with lower environmental impact, together with wide availability and chemical stability, and success has been achieved in utilizing Na 2 CO 3 in the production of normal-strength geopolymer (Krivenko, 1994;Xu et al, 2008;Abdalqader et al, 2016;Akturk et al, 2019). It is noted that Na 2 CO 3 is exclusively manufactured by the Solvay process, where the CO 2 in the air can even be captured and reduced (Lackner, 2002;Huijgen and Comans, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Na 2 SiO 3 , sodium carbonate (Na 2 CO 3 ) can be a promising substitution with lower environmental impact, together with wide availability and chemical stability, and success has been achieved in utilizing Na 2 CO 3 in the production of normal-strength geopolymer (Krivenko, 1994;Xu et al, 2008;Abdalqader et al, 2016;Akturk et al, 2019). It is noted that Na 2 CO 3 is exclusively manufactured by the Solvay process, where the CO 2 in the air can even be captured and reduced (Lackner, 2002;Huijgen and Comans, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of slag is initiated by the dissolution of the solid powder in the presence of an alkaline activator, followed by the formation of magnesium aluminum hydrotalcite (i.e. referred to as "hydrotalcite" throughout the manuscript) and the polycondensation of C-(A)-S-H with a low C/S ratio [2][3][4][5][6]. The alkaline activators commonly used in AAS mixes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Kovtun et al [34] also reported approximately 8 MPa and 23 MPa increase when SH was used as 20% and 50% replacement of the SC. The study by Akturk et al [28] where SH was used up to 40% replacement of SC also showed an enhancement in the early age compressive strength. The effect of various replacement levels of SC with SH on the 7 days compressive strength of SC activated slag from various studies is presented in Figure 7.…”
Section: Sodium Hydroxidementioning
confidence: 90%
“…Calcium hydroxide also referred to as hydrated lime or slaked lime (LM) is one of the additives that can be incorporated into SC activated slag to reduce the carbonate ions and increase the alkalinity of the system [23]. The study by Akturk et al [28] showed that the use of LM as a 3% replacement of the slag in SC activated slag resulted in significant enhancement of the early age compressive strength as presented in Figure 2. The presence of LM in the system also increases the rate and amount of calcium aluminate silicate hydrate formation which is a reaction that contributes to the strength capacity of the composite [24].…”
Section: Calcium Hydroxidementioning
confidence: 99%
See 1 more Smart Citation